Neuropathic pain-alleviating effects of pyrazole-conjugated arylsulfonamides as 5-HT6 receptor antagonists - Hong, Jin Ri; Choo, Hyunah; Nam, Ghilsoo (Pergamon Press Ltd., 2017)
A novel series of arylsulfonylaminomethyl-3-(1-phenyl-5-isopropyl)pyrazoles was evaluated for serotonin receptor subtype 6 (5-HT6R) antagonistic effects in vitro. We also investigated their neuropathic pain-alleviating effects in vivo using a rat spinal nerve ligation (SNL) model. Bicyclic aromatic sulfonamino groups, such as naphthalene and quinolin-substituted derivatives, showed good 5-HT6 inhibitory activity in vitro. Among them, selected compounds, 12 and 13, having 8-quinoylsulfonamino groups, showed potent neuropathic pain-alleviating effects in the rat model. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: ALZHEIMERS-DISEASE; MEMORY; RAT